Characterisation of Nano-Calcium Citrate from Waste Broiler Chicken Bones Synthesized Using Lime as a Novel Food Supplement - Prayitno, Agus Hadi; Umam, Muhammad Syafi’ul; Ridho, Muhammad Riziq; Safitri, Aisyah Rahmadani; Roihan, Naufal Alief (Buletin Peternakan, 2025)
Broiler chicken bone calcium oxide is 5.6 g mixed with 20 mL of distilled water. A mixture of 50 mL of lime juice and 30 mL of distilled water was added and then stirred using a hotplate magnetic stirrer at a temperature of 75°C for 30 min at a speed of 500 rpm/min. Ethanol 50% was added to as much as 20 mL (v/v), dried in the sun for 5 d, and then ground using a blender. Parameters observed were particle-size analysis (PSA), scanning electron microscopy (SEM), energy dispersive x-ray (EDX), fourier transform infrared (FTIR), and color. Data from PSA, SEM, EDX, FTIR, and color test results were analyzed descriptively. The research results show that green synthesis with lime can change the particle size of broiler chicken bone calcium into nanoparticles. Lime can be used to synthesize broiler chicken bone calcium into nano-calcium citrate with a particle size of around 524.1 nm. Colorimetric evaluation showed excellent brightness (L* 72.60), minimal redness (a* 3.20), moderate yellowness (b* 15.60), and acceptable whiteness (68.31), demonstrating lime's dual function as both a synthesizing agent and natural purifier. These findings indicate that the lime-mediated synthesis produces high-quality nano-calcium citrate from poultry byproducts, making it a promising candidate for novel food supplement applications.